Diversity of coral-associated pit crabs (Crustacea: Decapoda: Cryptochiridae) from Hong Kong, with description of two new species of Lithoscaptus A. Milne-Edwards, 1862 - Wong, Kingsley J. H.; Tsao, Yao-Feng; Qiu, Jian-Wen; Chan, Benny K. K. (Frontiers in Marine Science, 2023)
Highly specialized cryptochirid crabs are obligate symbionts of scleractinian corals in tropical and subtropical seas. General morphologies of cryptochirid crabs remain poorly described due to their small size and difficulties in collection; thus, the current inventory is probably an underestimation. In the present study, we sampled cryptochirid crabs from coral communities in Hong Kong. In the literature, only Cryptochirus hongkongensis (now Neotroglocarcinus hongkongensis) with unknown hosts had been recorded in Hong Kong since 1936. In addition to morphological examination, identification in the present study is further supported by sequence divergence of mitochondrial cytochrome c oxidase I (COI) and 16S ribosomal DNA markers. Six operative taxonomic units (OTUs), representing four species and one species complex with two species, were revealed among our material: Cryptochirus coralliodytes, Lithoscaptus paradoxus, Lithoscaptus doughnut sp. nov., Lithoscaptus scottae sp. nov., and Xynomaia sheni species complex. Morphological description of these species is provided, including description of the two new pseudocryptic species. The hosts of the genus Lithoscaptus belong largely to the Merulinidae, while L. doughnut sp. nov. inhabits the Plesiastreidae.